Assessment of Principals Practice of Leadership Behaviors in Some selected Primary Schools of Sodo Town Administration (Global Journal of Management and Business Research, 2016)
The Main purpose of this research is to investigate the extent to which primary school principals' practice leadership behaviors at primary schools of Sodo town Administration. For this purpose the researcher using purposive sampling to select four primary schools among primary schools found in the town administration. In these schools 63 teachers 9 principals were taken as a sample of the study. Information collected using questionnaire and interview were analyzed through using frequency and percentage. Based on the analysis and interpretation of data the result found indicated that the majority of principals does not have adequate leadership practice in their respective schools. Due to limited leadership ability and skill, work load, complexity of their task and low awareness of society to instructional leadership and students disciplinary problems. Finally based on the analysis and interpretation of data principals found to be medium practicing leadership behavior in their schools. This needs to be further improved to achieve the success of primary schools in all aspects of teaching learning process which intern brought change in all primary schools of Sodo town administration.
Keywords: leadership ability and skill; work load; complexity of their task and low awareness of society